Peloptulus borgesi - Nunes, Rui (2021)
JUSTIFICATION: Peloptulus borgesi is an endemic species of the Azores (Portugal), described from the island of S. Miguel. From the species description, it would have a very small Extent of Occurrence (4 km²) and Area of Occupancy (4 km²), which are likely underestimates, as this species probably has a wider distribution through the soil component of the island. It can be assumed that this species is affected by human activities and invasive plant species like Hedychium gardnerianum and Clethra arborea, which alter the natural structure and composition of the soil. Future climatic changes and increased risk of droughts will also affect this species. However, the present situation of this species needs to be further assessed and further research is needed into its population, distribution, threats, ecology and life history. Conservation of natural habitats and invasive species control could potentially aid this species' conservation. Based upon the incomplete knowledge regarding this species population, distribution, threats and ecology, this species is assessed as Data Deficient (DD).